Incidental maternal findings on fetal MRI. Issue 5 (May 2023) - Ruiz, M.; Wilson, M.P.; Randhawa, S.; Low, G.
Abstract : AIM: To evaluate the type and frequency of maternal findings incidentally identified during fetal magnetic resonance imaging (MRI). MATERIALS AND METHODS: A retrospective single-centre study was undertaken which included all consecutive fetal MRI studies performed between July 2017 and May 2021 at a tertiary institution. Two fellowship-trained radiologists reviewed the studies independently to determine the type and frequency of incidental maternal findings of both no clinical significance (requiring no further follow-up) and of clinical significance (requiring further follow-up, work-up, and/or management). Differences in acquisition were resolved by two-reader consensus. Non-diagnostic MRI examinations or abdominal MRI examinations indicated for maternal complications were excluded from review. RESULTS: A total of 455 consecutive fetal MRI examinations performed in 429 women were included. Mean age was 30 years (SD 5.5 years). At least one incidental maternal finding was identified in 58% (265/455) of studies. Umbilical hernias (35%), maternal hydronephrosis (19%), and maternal hydro-ureter (15%) were the most common. Only two studies (0.5%) showed clinically significant incidental maternal findings (pancreatic pseudocyst and ovarian cyst). CONCLUSIONS: Incidental maternal findings are common on fetal MRI but rarely require further follow-up, work-up, and/or management. Highlights: Incidental maternal findings were identified in over half of fetal MRs. Most findings were of low clinical relevance and related to pregnancy. Two patients had findings that altered management or follow-up. Findings had no correlation with patient's age, number of fetuses or trimester.